Contextualizing Thermal Effluent Impacts in Narragansett Bay Using Landsat-Derived Surface Temperature - Benoit, Jonathan; Fox-Kemper, Baylor (Frontiers in Marine Science, 2021)
This work utilizes remotely sensed thermal data to understand how the release of thermal pollution from the Brayton Point Power Station (BPPS) affected the temperature behavior of Narragansett Bay. Building upon previous work with Landsat 5, a multi-satellite analysis is conducted that incorporates 582 scenes from Landsat 5, Landsat 7, and Landsat 8 over 1984–2021 to explain seasonal variability in effluent impacts, contrast data after the effluent ceased in 2011, identify patterns in temperature before and after effluent ceased using unsupervised learning, and track how recent warming trends compare to the BPPS impact. Stopping the thermal effluent corresponds to an immediate cooling of 0.26 ± 0.1°C in the surface temperature of Mt. Hope Bay with respect to the rest of Narragansett Bay with greater cooling of 0.62 ± 0.2°C found near Brayton Point; though, cooling since the period of maximal impact (1993–2000) totals 0.53 ± 0.2°C in Mt. Hope Bay and 1.04 ± 0.2°C at Brayton Point. During seasons with lower solar radiation (winter) and lower mean river input (autumn and late summer), the BPPS effluent impact is more prominent. The seasonal differences between the high impact and low impact periods indicate that river input played an important role in the heat balance when emissions were lower, but surface fluxes dominated when emissions were higher. Putting the BPPS effluent in context, Landsat data indicates that Narragansett Bay warmed 0.5–1.2°C over the period of measurement at an average rate of 0.23 ± 0.1°C/decade and that net warming in Mt. Hope Bay is near zero. This trend implies that Narragansett Bay has experienced climatic warming over the past four decades on the scale of the temperature anomaly in Mt. Hope Bay caused by the BBPS effluent.